Self-care activities, sociodemographic variables, treatment and depressive symptoms among older adults with Diabetes Mellitus - Fernanda Auxiliadora Trevizani; Daniella Tech Doreto; Gabriella Santos Lima; Sueli Marques (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: to analyze the association between self-care activities of older adults with Type 2 Diabetes Mellitus (DM) and sociodemographic variables, type of treatment and depressive symptoms. Method: inferential and cross-sectional study, with 121 older adults with Type 2 DM in ambulatory care. We used a questionnaire for characterization of sociodemographic and health, questionnaire self-care activities with DM, Mini Mental State Examination and Geriatric Depression Scale. The association of variables was used (Fisher's exact test) and for comparing the means (Student's t-test and analysis of variance). Results: The mean age was 68.1 years, the majority were women (57.2%), retired (71.9%) and married (65.3%). The highest averages were for the activities: "to dry the spaces between the toes, after washing them" and smaller averages for "exercise". Conclusion: In spite of high average for self-care activities, there is a need for enhanced performance and compliance to them.